Pengaruh Model Project Based Learning (PJBL) Terhadap Kemampuan Berpikir Kritis Siswa Kelas XI pada Mata Pelajaran Sejarah di SMA Negeri 17 Kabupaten Tangerang - Syahriza Arif Lubis; Eko Ribawati; Arif Permana Putra (CV. ULIL ALBAB CORP, 2026)
The research aims to determine the effect of the application of the Project Based Learning (PjBL) model on the critical thinking skills of grade XI students in History subjects at SMA Negeri 17 Tangerang Regency. The method used in this research is a quasi-experimental method using the nonequivalent control group design. The sampling technique in this research was purposive sampling with XI.2 class of 50 students as the experimental class using the PjBL model and XI.1 class of 50 students as the control class using the Discovery Learning model. Hypothesis testing was carried out using a two-tailed t-test with the pooled variance formula. The results of the t-test analysis obtained (5.04) > (1.98) with a significance level of 0.05, then H0 is rejected Ha is accepted, meaning that there is an effect of the PjBL model on students' critical thinking skills in History subjects that focus on the material of the Indonesian National Movement. The PjBL model can be recommended as a learning model used in history learning because it is able to reconstruct student knowledge, through the skills of observing, analyzing, and synthesizing information aiming to foster a deeper understanding of historical events. In addition, PjBL focuses on a product-oriented problem-solving process, so it is effective in improving critical thinking skills.